Microclimatic and physiological analysis in coffee-cardamom mixed cropping system - YADUKUMAR, RAJENDRA HEGDE, M M HOSMANI, V S KORIKANTHIMATH, S J ANKEGOWDA, N (Journal of Spices and Aromatic Crops, 1998)
Experiments were conducted at Chettalli (Karnataka, India) to study microclimatic and gas exchange parameters in coffee (Coffea robusta) and cardamom (Elettaria cardamomum) mixed cropping system. Coffee in monocrop and mixed cropping systems recorded higher light interception, photosynthetically active radiation, net photosynthetic rate and transpiration rate compared to cardamom. In the mixed cropping system, cardamom received 57.8%’ light and almost equal amount of photosynthetically active radiation.